Validation of a newly developed mini-knemometer for premature infants - Rotzoll, Daisy E.; Pflüger, Marlene Sabine; Thiele, Antje Martina; Linderkamp, Otwin (Annals of human biology, 1999)
A newly developed knemometric device for lower leg length measurement in premature and newborn infants is presented and validated. The present study was performed to establish a standardized method of use of this instrument. Two independent observers obtained 10 subsequential readings per measurement in three infants over 43 days, after which analysis showed that 5 subsequential readings per measurement gave comparable technical errors. Thirty-one premature infants were assessed by knemometry by two independent observers. The correlation coefficient of all measurements was 0.998. The acquired technical error (mean Standard Deviation (SD) of 5 sequential readings) over a total observation period of 294 days in all studied infants was 0.06 and 0.05mm, respectively. By a mean lower leg length growth velocity of 0.52mm per day the technical error amounted to 11% of daily bone growth. The described mini-knemometer is an accurate device for the detection of daily individual growth. A learning period of 21 days is necessary to obtain reliable results.
Published online: 09 Jul 2009
Gesehen am 11.01.2021